Identification of a novel sequence type of Escherichia coli as the causative agent of pyelonephritis and bloodstream infection. Issue 5 (October 2016) - Mac Aogáin, Micheál; Miajlovic, Helen; Moloney, Geraldine; Chotirmall, Sanjay H.; Rogers, Thomas R.; Smith, Stephen G. J.
Abstract : Introduction: Globally, extra-intestinal pathogenic Escherichia coli are one of the predominant causative agents of bacteraemia. Case presentation: This case report outlines a presentation of community-acquired pyelonephritis and secondary bloodstream infection in an 81-year-old man. Laboratory investigations revealed that the causative isolate was a multi-drug-resistant E. coli of a novel multi-locus sequence type. This sequence type (ST) was designated ST-458 and was most closely related to the globally prevalent ST-131 lineage. Conclusion: This is the first report of a novel E. coli ST, ST-458, which caused pyelonephritis and bacteraemia.